Buildingthe User-Oriented Information Service Systemof Smart City - Shuguang Lin; Yanhui Guo; Yunyong Zhang; Xiaoming Chen (Dianxin kexue)
With the deve1opment of information techno1ogy and the growth of the smart city, the pub1ic demand for information techno1ogy more persona1ized and diversified, and higher requirements for the information services of the smart city are put forward.The existed prob1ems of current citizen information services were ana1yzed, and then the objects,contents and main features of smart city information service system were described.To conc1ude,it is feasib1e to bui1d the user-oriented information service system of smart city and the citizen homepage as its p1atform, and the pub1ic homepage connotation, service mode1, design thinking and p1atform architecture were e1aborated on.Fina11y, the deve1opment of the smart city information services were recommended.